The Kingdom of Maysan and its civilizational impact through the ages [Historical Study] - Abdul Ali Ghylan Al-Rubaiey, Hussein (Journal of College of Education, 2020)
The study of the history of the Kingdom of Maysan and its civilizational impact requires knowledge of the historical depth and natural extension of this spot throughout the various ages since its first inception through its various stages and in various eras and standing at the origin of its name and knowledge of some important cities, some of which are still visible and also some of its rivers that still bear their same names since The most ancient times and the accompanying world historical events coincided with the presence of large empires and the results generated by the surrounding circumstances in various stages and the birth of that Kingdom of important personalities that left a great impact in all aspects and civilizational fields, which became the starting point and S cultural pulation who inherited .